Improving Digital Assessment Practice: A Case Study of a Cross-Institutional Initiative - Chase, Anne-Marie; Ross, Bella; Robbie, Diane (Journal of University Teaching and Learning Practice, 2017)
Assessment practice is a crucial component of higher education learning and teaching, however many academic teachers lack formal teaching qualifications and often fall back on teaching and assessing the way they themselves were taught. Furthermore, with increasingly diverse student cohorts, larger classes and increasing components of teaching delivered online, it is unsurprising that students rate assessment as one of the poorest features of their learning experiences. For these reasons, understanding the specific contexts of assessment is important now more than ever. This paper will present the findings of a case study of a cross-institutional initiative aimed at exploring how to improve digital assessment practice by focusing on context, and encouraging and facilitating collegial collaboration. The aim of the case study was to progress a digital assessment project at an Australian higher education provider. Teams of staff from two higher education providers collaborated to develop and implement eight prototype assessments to reform digital assessment practices. The assessments were selected from online undergraduate academic subjects across a range of disciplines. Findings reveal that both staff and students felt that there were benefits to the cross-institutional collaboration. The resulting assessment was perceived as improving student motivation and engagement and more tailored for the online environment than the existing assessment.